Kajian timbulan sampah untuk menentukan produksi sampah rumah tangga dan evaluasi kapasitas TPS (studi kasus: kelurahan Jemmpong Baru-Mataram) - I.M. Suartika; S. Syahrul; M. Mirmanto; M. Wirawan (Universitas Mataram, 2021)
TPS is a temporary shelter of garbage before it is transported or disposed of to landfill. In order for TPS to accommodate garbage, it is necessary to know the volume of garbage to be served. This study aims to; firstly knowing the occurrence of household waste produced in the village of Jempong Baru, the second conducts an evaluation of the feasibility of TPS capacity to temporarily accommodate the waste produced based on the results of the study. The method used is descriptive method by conducting garbage survey based on SNI-19-3964-1994 and TPS capacity evaluation based on PERMEN PU RI No. 03/PRT/M/2013. From the results of the study obtained the emergence of household waste produced by the community in the village of Jempong Baru 6183 kg / day or 41907 liters / day equal to 41.9 m3 / day. Organic waste 3779 kg / day, plastic waste 572.5 kg / day, other non-organic waste 1775 kg / day. Then the results of measurement and evaluation of existing TPS with a capacity of 32 m3 with a waste ritasi one rate per day. So the existing TPS capacity is not enough to accommodate the volume of waste produced per day as much as 41.9 m3. The TPS capacity should be greater than the volume of waste produced. The results of this study are very useful to make improvements to the waste management system in Mataram city and especially in the village of Jempong Baru which is efficient and effective.